Göbekli Tepe, Turkey. A brief summary of research at a new World Heritage Site (2015–2019) - Clare, Lee (e-Forschungsberichte des DAI, 2020)
Göbekli Tepe ( 9.500–8.000 calBC) is a prehistoric site in Southeast Turkey that dates back to an early stage in the transition from hunter-gathering to farming economies in the Near East. Research undertaken in the period 2015–2019 has included the excavation of deep-soundings and the re-evaluation of some two decades of excavation records. This work is leading to a revision of former interpretations of the prehistoric site which still fuel the popular media image of Göbekli Tepe as home to the »World’s First Temples«.